Politik Pendidikan Indonesia: - Hasse J.; Mustaqim Pabbajah (IAI Darussalam, 2018)
This paper explores the problem of inequality in education in Indonesia. Educational facilities have stood firm and can be found up to the district city, its existence cannot be utilized optimally by the nation's children. The high school graduates who want to go to college, can not realize their dreams because of various obstacles. First, the adequacy of information about higher education is not evenly distributed. Access to information is more known to certain circles so that they can also choose institutions as a place to continue education. Information on scholarships, for example, is very limited. Second, the standard of acceptance used by higher education institutions is still 'unbalanced'. Competition for entry to the best colleges is only contested by graduates who come from the best schools as well. Graduates from certain schools, especially those away from access to education, are unable to compete and are marginalized. Third, the design of educational institutions is still ambiguous. The existence of the dichotomy of the state-private, common-religion, modern-traditional and various another naming also influenced the practice of the gap of the Indonesian higher education to the present. Higher education should be a space for all children of the nation and provide services without discriminating treatment